2015
DOI: 10.1126/science.aaa3655
|View full text |Cite|
|
Sign up to set email alerts
|

Shared regulatory programs suggest retention of blastula-stage potential in neural crest cells

Abstract: Neural Crest cells, unique to vertebrates, are derived from the ectoderm but also generate mesodermal cell types. This broad developmental potential persists past the time when most ectoderm-derived cells have become lineage restricted. The ability of neural crest to contribute mesodermal derivatives to the bauplan has raised questions about how this apparent gain in developmental potential is achieved. Here we describe shared molecular underpinnings of potency in neural crest and blastula cells. We show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
131
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(156 citation statements)
references
References 33 publications
13
131
0
1
Order By: Relevance
“…It is also noteworthy that a pool of multipotent postmigratory NC progenitors (47,48), some of which express cKit (49), has been recorded in other tissues; hence, it would be interesting to examine their relationship to CNC kit . Our study differs from a recent cardiac genetic fate-map of cKit, using different cKit alleles (21).…”
Section: Discussionmentioning
confidence: 99%
“…It is also noteworthy that a pool of multipotent postmigratory NC progenitors (47,48), some of which express cKit (49), has been recorded in other tissues; hence, it would be interesting to examine their relationship to CNC kit . Our study differs from a recent cardiac genetic fate-map of cKit, using different cKit alleles (21).…”
Section: Discussionmentioning
confidence: 99%
“…This model for extensive cross-talk between Hoxa1 and the pluripotency network may have relevance beyond ES cells. Recent studies in Xenopus have shown that many features of the regulatory program that controls pluripotency in the blastula are also present in neural crest cells (47). Because Hox genes, including Hoxa1, are known to play important roles in formation and patterning of neural crest cells (48,49), they may have a similar cross-regulatory interaction with the pluripotential network in this in vivo context.…”
Section: Resultsmentioning
confidence: 99%
“…Their induction and specification begins during the early gastrula stage of development and continues throughout organogenesis. This process depends on multi-module gene regulatory networks acting between the neural plate, non-neural ectoderm and paraxial mesoderm (Buitrago-Delgado et al, 2015;Hoppler and Wheeler, 2015;Huang and Saint-Jeannet, 2004;SaukaSpengler and Bronner-Fraser, 2008). Multiple signals and transcription factors are responsible for neural crest (NC) properties such as multipotency, induction, specification, migration and differentiation (Sauka-Spengler and Bronner-Fraser, 2008).…”
Section: Introductionmentioning
confidence: 97%